Yeast- and Mycelial-Phase Antigens of Blastomyces dermatitidis: Comparison Using Disc Gel Electrophoresis - Cox, Rebecca A. (Infect Immun, 1974)
The disc gel electrophoretic patterns obtained with skin test-active (mycelial and yeast) antigens of Blastomyces dermatitidis were compared. As would be expected, the blastomycins (mycelial-phase) and the cytoplasmic ultrafiltrates (yeast-phase) were heterogeneous mixtures containing proteins, glycoproteins, lipoproteins, and carbohydrates. The skin test-active cytoplasmic ultrafiltrates and the blastomycins contained glycoproteins that had similar R(f) values which allows the possibility that one or more of these components is responsible for the skin-test reactivity of these antigens. The electrophoretic migration of the alkali-soluble, water-soluble cell wall antigen differed from those of the cytoplasmic antigens and the two blastomycins. Electrophoresis, Sephadex chromatography, and ultrafiltration studies showed that the alkali-soluble, water-soluble cell wall antigen is comprised of lipid, polysaccharide, and protein and has a molecular weight range of 30,000 to 50,000. The increased number and mobility of both the protein and carbohydrate bands after denaturation and electrophoresis of this antigen in sodium dodecyl sulfate indicate that there are several cross-linkages between the polysaccharide and/or protein moieties, possibly via lipid or disulfide bridges.